2011
DOI: 10.1021/ma202115w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of High Molecular Weight and End-Functionalized Poly(styrene oxide) by Living Ring-Opening Polymerization of Styrene Oxide Using the Alcohol/Phosphazene Base Initiating System

Abstract: The ring-opening polymerization (ROP) of styrene oxide (SO) was carried out using 3-phenyl-1-propanol (PPA) as the initiator and a phosphazene base, 1-tert-butyl-4,4,4-tris(dimethylamino)-2,2-bis[tris(dimethylamino)phosphoranylidenamino]-2Λ5,4Λ5-catenadi(phosphazene) (t-Bu-P4), as the catalyst at room temperature. The polymerization proceeded in a living manner, which was confirmed by the kinetic and chain extension experiments, to produce the poly(styrene oxide) (PSO) with a controlled molecular weight (5200–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 25 publications
1
56
0
Order By: Relevance
“…This result indicated that t ‐Bu‐P 4 possessed sufficient basicity for the ROP of BO, while other organic superbases had no catalytic activity due to insufficient basicity. Moreover, it was anticipated that the polymerization of BO proceeded through a mechanism of chain end activation 6–8, 15…”
Section: Resultsmentioning
confidence: 99%
“…This result indicated that t ‐Bu‐P 4 possessed sufficient basicity for the ROP of BO, while other organic superbases had no catalytic activity due to insufficient basicity. Moreover, it was anticipated that the polymerization of BO proceeded through a mechanism of chain end activation 6–8, 15…”
Section: Resultsmentioning
confidence: 99%
“…In order to avoid metal contamination without any special purification steps, the organocatalytic approach has emerged as a powerful metal-free polymerization process in recent years. 7 Considerable effort has been directed toward the evaluation of various types of both organic acids/bases for the ROP of cyclic esters, 7-37 cyclic carbonates, [38][39][40][41][42][43] epoxides, [44][45][46][47] lactams, 48 cyclic (carbo)siloxanes, 49 cyclic phosphates, [50][51][52][53][54] etc. Regarding the ROP of cyclic esters, organic Brønsted acids, e.g., methane sulfonic acid (MSA) and triflimide, were found to be suited for the polymerization of lactones, [8][9][10][11][12][13][14][15][16][17][18][19] whereas organic bases, e.g., 1,8-diazadicyclo [5.4.0]undec-7-ene (DBU) and 4-dimethylaminopyridine (DMAP), were effective for the ROP of the lactide (LA).…”
Section: Introductionmentioning
confidence: 99%
“…These values are consistent with those reported in a number of articles about PSO. [19,20] Styrene oxide is notably less reactive than aliphatic and other alicyclic epoxides, but is known to undergo ring-opening with acids and bases. [4] Therefore, it is important to find suitable catalysts for styrene oxide to undergo ring opening polymerization through forming large molecular weights of polymers.…”
Section: Materials and Instrumentationmentioning
confidence: 99%